Pengaruh Practices Human Resource Management Dan Employee Service Quality Terhadap Competitive Advantage Dimediasi Employee Engagement Pada Jne Area Cikarang - Restu Amelia; Retno Purwani Setyaningrum (Peneliti.net, 2023)
Competitive Advantage, namely the ability gained through roles and resources to outperform an organization/company of a similar nature, and keep the company active and developing so that it is superior to its competitors. With the intense competition requires a company to be more competitive. This study aims to analyze human resource management practices and employee service quality on competitive advantage mediated by employee engagement in the JNE Cikarang area. This study found a comprehensive analysis of competitive advantage. The method used in this study uses the SmartPLS Version 3.0 application. Analysis of the 87 respondents in this study used cluster random sampling method. This study resulted that the practice of human resource management and employee service quality had no effect on competitive advantage, furthermore there was a significant positive effect between employee engagement on competitive advantage in the JNE Cikarang Area. The final results of this study reveal that human resource management practices have a positive effect on competitive advantage through employee engagement, as well as employee service quality have a positive effect on competitive advantage through employee engagement.